A limit approaching pop-up message reduces gambling expenditures, except among players with a financially focused self-concept. Issue 2 (4th May 2019) - Tabri, Nassim; Hollingshead, Samantha J.; Wohl, Michael J. A.
ABSTRACT: Responsible gambling (RG) tools that guide electronic gaming machine (EGM) players to set a pre-set money limit on their gambling expenditures are known to reduce excessive gambling. However, not all EGM players who use a limit-setting RG tool will adhere to their limit. We hypothesized that limit adherence is facilitated by informing players that their limit is approaching (and when their limit is reached), but undermined by a financially focused self-concept (FFS). Accordingly, EGM players (N = 88) were provided seed funds to gamble with on a slot machine in a simulated virtual reality casino. They were randomly assigned to receive a limit reminder both when their limit was approaching and again when their limit was reached (experimental condition) or just when their limit was reached (control condition). Players in the experimental condition were more likely to stop playing before reaching their money limit compared to players in the control condition. However, this was observed among players who are low, but not high, in FFS. Unexpectedly, condition (control vs experimental) was unrelated to playing beyond the money limit and FFS did not moderate this relation. Results suggest that individual difference factors, like FFS, can undermine the utility of RG tools.